أهمية الدور الاقتصادي للاسواق المالية مع التركيز على السوق العراقية للاوراق المالية (Al-Mansour Journal, 2023)
Most of under developing countries are facing the problem of funding. Manage of the academics and researcher believed that money markets can play an important role in the mentioned problem, hence those market can provide shares and which can enlarge the saving and attract low income consumers.The huge development of the money market in the field of law, manage met and communications resulted in Stratham the financial ability of the market which is the most important factor of development.This paper gives large light on the role of Iraqi security market in allocating financial resource and savers in the development process.